THE REPRESENTATION OF POWER AND DOMINATION IN ASSASSIN’S CREED: A MULTIMODAL CRITICAL DISCOURSE ANALYSIS - Clerensia Tian Sunarto; Albert Tallapessy; Sabta Diana (Universitas Sebelas Maret, 2019)
This study aims to reveal the power of dominant group which is from different social class and status. The data source is a movie entitled Assassin’s Creed which is downloaded from internet. The theory of Generic Structure is used to identify the elements of the movie and to collect the data. The data are analysed in the form of shots and clauses which is visual and linguistics element. The linguistics data are analysed by using Systemic Functional Linguistics (SFL) by Halliday (2004) the other hand, the visual data are analysed by using Systemic Functional Visual Element by Kress and Van Leeuwen (2006). Therefore, this research is Critical Discourse analysis (CDA) study. The research’s finding is the power that represents by the dominant people which is constructed in Assassin’s Creed.